Stakeholder Analysis in Maternal and Child Health Policy in Subang Regency - Ilhami, Rizky (International Publisher, 2023)
This research aims to analyze the stakeholders involved in implementing maternal and child health policies in Subang Regency. With a focus on the public health context, this research identifies key stakeholder groups that have an important role in the formulation, implementation and evaluation of maternal and child health policies. This research method uses a qualitative approach with descriptive methods. The research results show that the problem identification process in maternal and child health policy in Subang Regency involves various stakeholders, including government institutions, community groups and other institutions. The Subang District Health Service is proven to have great influence and high commitment, while the Regional Government Budget Team/TAPD, Civil Registry Office, and Family Planning are also actively involved. However, there are still weaknesses in completing the Regional Action Plan (RAD) as well as limited understanding of various policy alternatives. Therefore, further efforts are needed to strengthen commitment and increase mutual understanding in order to optimize policy steps that can reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in the region.